RELIGIOUS BELIEFS IN ONE MAN ONE WIFE (ALUKO, 1967) AND IN PURPLE HIBISCUS (ADICHIE, 2006) - CAPO-CHICHI ZANOU, LAURE CLÉMENCE (My University, 2017)
Religion is a universal phenomenon that is as old as the world, just as every people has its own culture so have they, their own religion that is culture-bound. In fact, religion is part and parcel of people’s culture, since it determines their way of life. In India, there are Buddhism and Hinduism among other religions; Europeans mainly practise Christianity and Judaism and Arabs are most of the time Muslims. In Africa, alongside the belief in a supreme entity whose name varies from one community to the other, there exist other lesser gods and goddesses. So, Africans have not heard about the concept of an omniscient God for the first time from Europeans, they know about it before the white men’s arrival. However, Africans still stick to their ancestral religious beliefs in lesser gods and goddesses, who, according to them, are the Almighty God’s messengers. Some African novelists allude to these beliefs in their texts. My intention in this paper is to dig out how religion appears in two selected African fictional works. I will deal with the main features of traditional religion on the one hand, and I will analyse some Christians’ intolerance and narrow-mindedness, on the other. The result I have come up with through the study of those two novels is that tolerance leads to the best harmonious cohabitation between modern and traditional religions. The absence of such tolerance is destructive to mankind.
Keywords: African religion; Christianity; Tolerance; Bigotry.